EVALUASI PROGRAM PENDIDIKAN BERBASIS KEMITRAAN DALAM MENINGKATKAN MUTU MADRASAH (Studi Kasus Prodistik di MAN 1 Ponorogo) - Muhadi, Muhadi (Ngabari: Jurnal Studi Islam dan Sosial, 2018)
This study aims to: (1) find out the Prodistik program evaluation model in MAN 1 Ponorogo, (2) criticize the Prodistik evaluation process in MAN 1 Ponorogo, and (3) understanding the constraints / barriers to Prodistik evaluation in MAN 1 Ponorogo. By using qualitative methods and collecting data on interview, observation and documentation techniques, it can be understood that the techniques applied in the implementation of the Prodistik evaluation are using tests, check lists of documents, and interviews from the ITS. This study produced findings: 1) Prodistik evaluation model in MAN 1 Ponorogo using the CIPP model, 2) Prodistik evaluation process in MAN 1 Ponorogo, starting from formulating objectives, selecting evaluation tools in the form of test questions, compiling test questions according to each class / semester, distributing test questions to work on students, assessing the results of student answers, following up prodistik based on the results of the evaluation in the form of a decision to continue prodistik and add field competency tests. 3) Constraints / barriers to Prodistik evaluation in MAN 1 Ponorogo) are lack of instructor staff and lack of facilities.